Structure and target interaction of a G-quadruplex RNA-aptamer. Issue 10 (2nd October 2016) - Szameit, Kristina; Berg, Katharina; Kruspe, Sven; Valentini, Erica; Magbanua, Eileen; Kwiatkowski, Marcel; Chauvot de Beauchêne, Isaure; Krichel, Boris; Schamoni, Kira; Uetrecht, Charlotte; Svergun, Dmitri I.; Schlüter, Hartmut; et al.
ABSTRACT: G-quadruplexes have recently moved into focus of research in nucleic acids, thereby evolving in scientific significance from exceptional secondary structure motifs to complex modulators of gene regulation. Aptamers (nucleic acid based ligands with recognition properties for a specific target) that form Gquadruplexes may have particular potential for therapeutic applications as they combine the characteristics of specific targeting and Gquadruplex mediated stability and regulation. We have investigated the structure and target interaction properties of one such aptamer: AIR-3 and its truncated form AIR-3A. These RNA aptamers are specific for human interleukin-6 receptor (hIL-6R), a key player in inflammatory diseases and cancer, and have recently been exploited for in vitro drug delivery studies. With the aim to resolve the RNA structure, global shape, RNA:protein interaction site and binding stoichiometry, we now investigated AIR-3 and AIR-3A by different methods including RNA structure probing, Small Angle X-ray scattering and microscale thermophoresis. Our findings suggest a broader spectrum of folding species than assumed so far and remarkable tolerance toward different modifications. Mass spectrometry based binding site analysis, supported by molecular modeling and docking studies propose a general Gquadruplex affinity for the target molecule hIL-6R.